Development and validation of the pain management competency scale for nurses and a nationwide survey of Chinese nurses - Yixue Wu; Xiang Pan; Lihui Gu; Yingge Tong; Siyi Chen; Ke Ni; Hangyan Du; Meng Yang; Jianyi Wang; Yi Chen; Yeling Wei; Lingling Luo; et al. (BMC Nursing)
Abstract Background Nurses’ competency in pain management is essential for effectively alleviating patients' acute pain, controlling chronic pain, and promoting patient recovery. However, reliable tools for evaluating these competencies across different clinical specialties and healthcare settings are lacking. This study aimed to develop and validate a Pain Management Competency Scale for Nurses (PMCSN) and to assess the pain management competencies of nurses in China through a nationwide survey. Methods An item pool and a draft scale were developed through literature reviews, semi-structured interviews, and expert panel discussions. This was followed by refinement of the scale via Delphi expert consultations and a pilot test. To validate the scale, 342 nurses were conveniently sampled from six hospitals in Eastern and Central China. The validation process included item analysis, internal consistency reliability assessment, test–retest reliability (with 40 nurses retaking the questionnaire after a 14-day interval), content validity (evaluated by six experts using a 4-point Likert scale), and structural validity (assessed through exploratory and confirmatory factor analyses). The validated scale was then applied in a survey of 1,500 nurses from 15 hospitals across Eastern, Central, and Western China. Statistical analyses included descriptive statistics, analysis of variance (ANOVA), and t-tests. Results The PMCSN comprised six primary dimensions—Pain Assessment and Monitoring, Pharmacological Pain Management, Non-Pharmacological Pain Management, Management of Analgesic Adverse Effects, Patient/Family Education, and Professional Development—and includes 52 tertiary items. The PMCSN scores ranged from 6 to 120, calculated by summing the standardized scores across the six dimensions, with higher scores indicating greater competency in pain management. The scale’s Cronbach’s α was 0.974 (dimension-specific values ranging from 0.863 to 0.935) and a test–retest reliability of 0.871. The content validity index (CVI) of the scale was 0.965. Exploratory factor analysis (EFA) showed that the six-factor model explained 67.50% of the variance. Confirmatory factor analysis (CFA) indicated good model fit, with average variance extracted (AVE) values ranging from 0.659 to 0.811 and composite reliability (CR) between 0.909 and 0.973, confirming good convergent validity. The square roots of the AVE values exceeded the inter-factor correlations, indicating good discriminant validity. In the nationwide survey, the average PMCSN score among 1,500 nurses was 101.27 ± 20.97. Nurses with higher education levels scored higher (F = 14.173, p < 0.01), as did those working in Eastern regions (F = 24.632, p < 0.01) and tertiary hospitals (T = -5.476, p < 0.01). Conclusions The PMCSN is a valid and reliable tool for assessing nurses’ pain management competencies. It provides a standardized approach for evaluation and guides targeted interventions to improve competency. Regional and hospital-level disparities highlight the need for enhanced training in underdeveloped areas and collaboration between hospitals to promote balanced healthcare resources.